Fear of COVID-19 when experiencing pregnancy or childbirth in the pandemic: what are the associated factors? - Ana Júlia de Paula; Paulo César Condeles; Jéssica Aparecida da Silva; Luciano Marques dos Santos; Luciana Mara Monti Fonseca; Mariana Torreglosa Ruiz; Monika Wernet (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to identify factors associated with fear of COVID-19 among women who experienced pregnancy or childbirth during the pandemic. Methods: a cross-sectional study, nested within a prospective cohort, using an online survey, from August 2021 to February 2022, based on descriptive data analysis. Results: of the 431 participants, 52.8% were postpartum women and 20.1% were pregnant women. With regard to fear of COVID-19, a mean score of 20.46 was obtained (moderate fear). The highest fear scores were present in women whose newborns were admitted to hospital in neonatal critical units (p=0.032), and the lowest among those covered by supplementary health (insurance) (p=0.016). Conclusion: among pregnant and postpartum women, high fear of COVID-19 translated into the possibility of having newborns admitted to hospital in a critical unit. The importance of supporting actions to support pregnant/postpartum women's mental health in relation to COVID-19 or other threats that may influence the neonatal outcome stands out.